2020
DOI: 10.1080/1461670x.2020.1758956
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Newsroom: Measuring Journalists’ Perceptions of Innovative Learning Culture

Abstract: Thorough understanding of how "outside the box" ideas in the newsroom can be triggered and fostered is fundamental to grasp innovation in journalism, but is still largely uncharted territory. Comprehension of its key elements would enable news organisations to reinvent themselves and improve chances for survival. In this article we develop an instrument to investigate if and how newsroom workers and management perceive an Innovative Learning Culture (ILC). This survey enables us to locate which aspects of ILC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
0
9
0
2
Order By: Relevance
“…The findings portray how change is notoriously hard to achieve in legacy media newsrooms (Villi et al 2020;Ekdale et al 2015;Ess 2014). However, our findings also point to a possible remedy: Building a strong PSCC could help media organizations in achieving a fertile environment for an innovative learning culture (ILC) that triggers and fosters much needed explorative innovation (Porcu 2017;Porcu, Hermans, and Broersma 2020). Supported by strong PSCC and ILC, legacy media newsrooms could be better equipped to ensure their long-term survival.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The findings portray how change is notoriously hard to achieve in legacy media newsrooms (Villi et al 2020;Ekdale et al 2015;Ess 2014). However, our findings also point to a possible remedy: Building a strong PSCC could help media organizations in achieving a fertile environment for an innovative learning culture (ILC) that triggers and fosters much needed explorative innovation (Porcu 2017;Porcu, Hermans, and Broersma 2020). Supported by strong PSCC and ILC, legacy media newsrooms could be better equipped to ensure their long-term survival.…”
Section: Discussionmentioning
confidence: 72%
“…However, innovation in the media industry is often incremental and focused on small improvements in products (Krumsvik et al 2019). Journalists' "creative energies", as Porcu, Hermans, and Broersma (2020) write, are sucked dry by the day-to-day news production that focuses on efficient output and short-term demand. Hence, legacy media organizations' innovation efforts are often exploitative (short-term, "inside the box") rather than explorative (long-term, "outside the box") even though, according to multiple researchers (Porcu 2017;Porcu, Hermans, and Broersma 2020;K€ ung 2015;Westlund and Lewis 2014), explorative innovation is what these organizations most desperately need in order to reinvent themselves and survive in the future.…”
Section: Creativity and Innovation In The Field Of Media And Journalismmentioning
confidence: 99%
“…The importance of putting the audience at the center of journalistic work and how that has changed journalists' approach to news stories might help these experiments become more common in news media. In journalistic literature, other innovative experiments have been observed during different periods of crisis; news organizations eventually adopted these experiments into their workflows (Belair-Gagnon & Steinke, 2020;Cavallo et al, 2020;Porcu et al, 2020). DOI: 10.25200/BJR.v17n2.2021.1369…”
Section: Discussionmentioning
confidence: 99%
“…This involves media workers (Deuze 2007) coordinating with each other across departments in working toward shared organizational goals-a far cry from some managerial approaches (common in the past) that separate members into distinct functional units and discourage them from communicating with each other. A recent Dutch survey with two news organizations found that "shared goals" was perceived as most important when it comes to fostering innovative learning cultures (Porcu, Hermans, and Broersma 2020), and a recent Finnish study found that a psychologically safe communication climate (PSCC) as well as intentional idea sharing and development habits were important to innovation (Koivula, Villi, and Sivunen 2020). Coordination of media work may include only limited cross-departmental communication by media workers who otherwise remain distant from one another; nevertheless, such efforts may also result in closer engagement across boundaries and thus generate a sort of Collaboration.…”
Section: Introductionmentioning
confidence: 99%